Lactobacillus plantarum possesses the capability for wall teichoic acid backbone alditol switching - Bron, Peter A (BioMed Central, 2012)
BACKGROUND: Specific strains of Lactobacillus plantarum are marketed as health-promoting probiotics. The role and interplay of cell-wall compounds like wall- and lipo-teichoic acids (WTA and LTA) in bacterial physiology and probiotic-host interactions remain obscure. L. plantarum WCFS1 harbors the genetic potential to switch WTA backbone alditol, providing an opportunity to study the impact of WTA backbone modifications in an isogenic background. RESULTS: Through genome mining and mutagenesis we constructed derivatives that synthesize alternative WTA variants. The mutants were shown to completely lack WTA, or produce WTA and LTA that lack D-Ala substitution, or ribitol-backbone WTA instead of the wild-type glycerol-containing backbone. DNA micro-array experiments established that the tarIJKL gene cluster is required for the biosynthesis of this alternative WTA backbone, and suggest ribose and arabinose are precursors thereof. Increased tarIJKL expression was not observed in any of our previously performed DNA microarray experiments, nor in qRT-PCR analyses of L. plantarum grown on various carbon sources, leaving the natural conditions leading to WTA backbone alditol switching, if any, to be identified. Human embryonic kidney NF-κB reporter cells expressing Toll like receptor (TLR)-2/6 were exposed to purified WTAs and/or the TA mutants, indicating that WTA is not directly involved in TLR-2/6 signaling, but attenuates this signaling in a backbone independent manner, likely by affecting the release and exposure of immunomodulatory compounds such as LTA. Moreover, human dendritic cells did not secrete any cytokines when purified WTAs were applied, whereas they secreted drastically decreased levels of the pro-inflammatory cytokines IL-12p70 and TNF-α after stimulation with the WTA mutants as compared to the wild-type. CONCLUSIONS: The study presented here correlates structural differences in WTA to their functional characteristics, thereby providing important information aiding to improve our understanding of molecular host-microbe interactions and probiotic functionality.